(untitled) (Research, Society and Development, 2021)
Dentofacial deformity is described as a condition in which the jaw bones are out of normal, where malocclusion exists and facial aesthetics are affected. This condition affects about 20% of the world population and requires an accurate diagnosis. Orthognathic surgery in combination with orthodontic treatment is the treatment of choice for the correction of dentofacial deformities, due to its high complexity, a multidisciplinary approach is necessary to perform such treatment. This paper aims to discuss the diagnosis and treatment of dentofacial deformities through a literature review and presentation of a clinical case. In the case reported, the patient with class III dentofacial deformity underwent orthodontic treatment and orthognathic surgery planned virtually using the Dolphin 3D software. After the surgical procedure, a significant improvement in facial harmony and occlusal stability was observed. Such results are maintained in a two-year postoperative follow-up. Virtual planning in orthognathic surgery is becoming increasingly important, allowing surgeons to simulate multiple options of jaw movements until the best results are obtained for the patient.